The Effect of Product Quality and Distinctiveness on Consumer Loyalty Mediated by Consumer Satisfaction - Hanif Mutiara Rohmah; Sunaryo; Nanang Suryadi (International Journal of Science and Society, 2023)
This research aims to analyze the effect of product quality, distinctiveness, and consumer satisfaction on consumer loyalty; examine the effect of product quality and distinctiveness on consumer loyalty mediated by consumer satisfaction. This research employed quantitative approach by using 190 customer of Sambel Pecel Karangsari Blitar as the sample. The sampling technique used in this research is accidental sampling in collecting the respondents and purposive sampling in choosing respondents with the criteria matched to the research objectives. Ordinary Least Square (OLS) and Path analysis are the method used to conduct the research analysis. The results showed product quality had significant positive influence on consumer loyalty; distinctiveness had significant positive influence on consumer loyalty; consumer satisfaction had significant positive influence on consumer loyalty; product quality had direct influence on consumer loyalty; distinctiveness had direct influence on consumer loyalty; there are direct and indirect influence of product quality on consumer loyalty through consumer satisfaction since the direct influence is greater than the indirect influence based on path analysis result; there is also a similar result of direct and indirect influence of distinctiveness on consumer loyalty through consumer satisfaction since the direct influence is greater than the indirect influence based on path analysis result. Sobel test proved that consumer satisfaction successfully acted as partial mediating variable.